2008
DOI: 10.1111/j.1601-5037.2007.00271.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral health‐related quality of life in children: Part III. Is there agreement between parents in rating their children’s oral health‐related quality of life? A systematic review

Abstract: Valid and reliable information can be obtained from parents and children using appropriate questionnaire techniques. Although the parents' reports may be incomplete due to lack of knowledge about certain experiences, they still provide useful information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
84
1
9

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(104 citation statements)
references
References 27 publications
6
84
1
9
Order By: Relevance
“…3 As such, mothers account for the highest percentage of proxy measures employed in studies of children's health. 1,2,[4][5][6][7] In a systematic review of parent-child agreement on ratings of children's oral health-related quality of life (OHRQoL), 8 only three studies assessed parent-child agreement regarding children's OHRQoL. 2,5,9 These studies were conducted with convenience samples in developed countries.…”
Section: Introductionmentioning
confidence: 99%
“…3 As such, mothers account for the highest percentage of proxy measures employed in studies of children's health. 1,2,[4][5][6][7] In a systematic review of parent-child agreement on ratings of children's oral health-related quality of life (OHRQoL), 8 only three studies assessed parent-child agreement regarding children's OHRQoL. 2,5,9 These studies were conducted with convenience samples in developed countries.…”
Section: Introductionmentioning
confidence: 99%
“…A esta edad, comienzan a comparar sus características físicas y trazos de personalidad con las de otros niños. Su capacidad de realizar juicios sobre su apariencia, calidad de las amistades, pensamientos de otras personas, emociones y comportamiento se desenvuelve padres (9,10). A pesar de que los instrumentos desarrollados para medir la CV deberían ser respondidos por los propios niños, que tienen el derecho de expresar sus opiniones y de hacerlas respetar, en el caso de preescolares los instrumentos son generalmente respondidos por los responsables.…”
Section: Percepción De Niños Y Padres Sobre La Cvrsbunclassified
“…Los relatos ofrecidos por los padres sirven de gran valor a la hora de evaluar la CVRSB en preescolares. Se entiende que, mientras más graves sean las alteraciones patológicas, más estrecha será la relación entre padres e hijos, de forma que esos estén más familiarizados con las actividades y sentimientos de sus hijos (9).…”
Section: Percepción De Niños Y Padres Sobre La Cvrsbunclassified
See 1 more Smart Citation
“…It was found that parents or caregivers had a limited view of the oral health status of their children. [14][15][16] Thus, parents/caregivers interviewed in studies involving the use of the ECOHIS may have had difficulty recognizing the contribution of malocclusion to…”
mentioning
confidence: 99%